2017
DOI: 10.18621/eurj.342109
|View full text |Cite
|
Sign up to set email alerts
|

Determination of minimum serum concentration to develop scaffold free micro-tissue

Abstract: Objective. Formation of three-dimensional (3D) micro-tissues without scaffolds are widely used not only to define in vivo tissue formation mechanisms but also the development of different tissue-specific drugs. However, depending on high serum and growth factor concentrations, it would be hard to identify major effective biological cues on micro-tissue formation. The aim of the study is to determine the effect of different serum concentrations on Human Umbilicial Vein Endothelial Cells (HUVECs) micro-tissue fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…At the end of 7th day, less efficacy was seen in 3 mM YIGSR peptide concentration compared with 1.5 mM peptide concentration. Studies of Martin et al [26], Karaman and Yarali [27], and Yarali et al [28] demonstrated that formation of SFMs develops depending on the diameter enlargement of SFMs. In light of that information, we concluded that both of YIGSR peptide concentrations provide enlargement of HUVEC SFMs and contributed to developing SFMs formation until the end of the 4th day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the end of 7th day, less efficacy was seen in 3 mM YIGSR peptide concentration compared with 1.5 mM peptide concentration. Studies of Martin et al [26], Karaman and Yarali [27], and Yarali et al [28] demonstrated that formation of SFMs develops depending on the diameter enlargement of SFMs. In light of that information, we concluded that both of YIGSR peptide concentrations provide enlargement of HUVEC SFMs and contributed to developing SFMs formation until the end of the 4th day.…”
Section: Discussionmentioning
confidence: 99%
“…Martin, F. et al showed that the differentiation state and development of the generated SFMs can be identified by diameter calculation and SFMs maturation [26]. Moreover, Karaman and Yarali [27] demonstrated that SFMs diameter measurement can relate to SFMs growth and viability analysis. Therefore, diameter analysis can be used to identify healthy growing SFMs [27,28].…”
Section: Early Onlinementioning
confidence: 99%
See 2 more Smart Citations
“…This could be due to the formation of protein corona on the GO surface which in turn influence the toxicity of GObased materials [61,62]. Furthermore, studies have indicated that serum proteins can have an interfering effect on interactions between nanoparticles, cells and biological molecules [63][64][65]. Accordingly, Lesniak et al [64] demonstrated that various protein corona formed on silica nanoparticles modified cell adhesion, cellular uptake, and toxicity, which is determined by the serum protein concentration.…”
Section: Discussionmentioning
confidence: 99%